2003
DOI: 10.4315/0362-028x-66.6.1030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Consumer-Style Cooking Methods for Reduction of Escherichia coli O157:H7 in Ground Beef

Abstract: The objective of this study was to evaluate the thermal inactivation of Escherichia coli O157:H7 in ground beef cooked to an internal temperature of 71.1 degrees C (160 degrees F) under conditions simulating consumer-style cooking methods. To compare a double-sided grill (DSG) with a single-sided grill (SSG), two different cooking methods were used for the SSG: for the one-turnover (OT-SSG) method, a patty was turned once when the internal temperature reached 40 degrees C, and for the multiturnover (MT-SSG) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 21 publications
2
28
0
1
Order By: Relevance
“…2). It is recommended that hamburgers reach an internal temperature of 71.1°C (26), but undercooked hamburgers are a frequent cause of EHEC infections (18). We found that at 60°C, the matrix seemed to have an effect on the inactivity.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…2). It is recommended that hamburgers reach an internal temperature of 71.1°C (26), but undercooked hamburgers are a frequent cause of EHEC infections (18). We found that at 60°C, the matrix seemed to have an effect on the inactivity.…”
Section: Discussionmentioning
confidence: 52%
“…Thermal inactivation is regarded as a central postprocessing method for reducing the level of STEC in food, and several food-borne outbreaks are due to undercooked beef or ground beef (12,26). As expected, heating also reduced the infectivity of the phages, and the reduction was faster at the highest temperature (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…Enumeration of injured E. coli O157:H7 was accomplished with phenol red agar base with 1% sorbitol (SPRAB) (14). After 37°C, 24 h of incubation, typical white colonies were enumerated and, simultaneously, serological confirmation using a RIM E. coli O157:H7 latex agglutination test (Remel, Lenexa, KS) was performed on randomly selected presumptive colonies of E. coli O157:H7.…”
Section: Methodsmentioning
confidence: 99%
“…Following incubation, presumptive colonies of S. Typhimurium with typical black colonies were enumerated. For enumerating injured cells of E. coli O157:H7, phenol red agar base with 1% sorbitol (SPRAB; Difco) was used (24). After incubation at 37°C for 24 h, typical white colonies characteristic of E. coli O157:H7 were enumerated.…”
Section: Methodsmentioning
confidence: 99%